Rancang Bangun Sistem Informasi Rekam Medis Pasien Rawat Jalan (Studi Kasus Praktek Dokter Spesialis Apotek Cipta Pontianak) - Rusmiani, Rusmiani; Hidayati, Awanis (Jurnal Kridatama Sains dan Teknologi, 2024)
The objective of this research is to analyze and develop an information system capable of processing large volumes of patient medical records. This system will facilitate the data processing for creating patient medical record reports, which are currently managed manually. This study employs a mixed-methods research approach, utilizing both primary and secondary data. Primary data were obtained through interviews, questionnaires with respond-ents, and documentation at the research site, while secondary data were sourced from relevant books and publications. The system development follows the Waterfall methodology. The results of this research indicate that a web-based Outpatient Medical Record Information System, exemplified in the case study of an ENT specialist's practice at Cipta Pharmacy Pontianak, was successfully developed and tested using black-box testing and usability testing. The usability testing was evaluated based on variables such as learnability, memorability, efficiency, error rate, and satisfaction. The test results show that the information system achieved an overall average score of 3.45, placing it in the very good interval category.